2011
DOI: 10.1063/1.3598962
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the nonadiabatic rotational excitation process in a symmetric-top molecule induced by two intense laser pulses

Abstract: We experimentally investigate the nonadiabatic rotational excitation process of a symmetric-top molecule, benzene, in the electronic ground state irradiated by intense nonresonant ultrafast laser fields. The initial rotational-state distribution was restricted mostly to the five lowest levels with different nuclear spin modifications by an extensive adiabatic cooling with the rotational temperature well below 1 K, and distributions after the interaction with a femtosecond double-pulse pair (3-5 TW/cm(2) each w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 50 publications
0
13
0
1
Order By: Relevance
“…Daems et al [565] showed that a combination of a half-cycle pulse and a short nonresonant laser pulse produces a strongly enhanced post-pulse orientation. Baek et al [566] studied the field-free dynamics of benzene aligned by two consecutive short laser pulses, while the interaction of rotationally excited molecules with short laser pulses was studied by Owschimikow et al [567][568][569]. Yun et al [570] analyzed the time evolution of the quantum phases of the rotational states contributing to the rotational wave packet which provided new insights into the post-pulse alignment dynamics.…”
Section: Interaction With Short Laser Pulses: Nonadiabatic Alignment ...mentioning
confidence: 99%
“…Daems et al [565] showed that a combination of a half-cycle pulse and a short nonresonant laser pulse produces a strongly enhanced post-pulse orientation. Baek et al [566] studied the field-free dynamics of benzene aligned by two consecutive short laser pulses, while the interaction of rotationally excited molecules with short laser pulses was studied by Owschimikow et al [567][568][569]. Yun et al [570] analyzed the time evolution of the quantum phases of the rotational states contributing to the rotational wave packet which provided new insights into the post-pulse alignment dynamics.…”
Section: Interaction With Short Laser Pulses: Nonadiabatic Alignment ...mentioning
confidence: 99%
“…Using phase-shaped femtosecond ionizing laser pulses Hertz et al reported excitation of only odd J states of the O molecule, and achieved alignment of 0.86 at 60 K 25 . Experimental investigation of the nonadiabatic rotational excitation for ground state symmetric-top molecules, by two intense nonresonant ultrafast laser fields, leads to excitation of states if while and if 26 . Hirokazu et al calculated the time evolution of the rotational-state distribution for NO molecules at varying pump intensities 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Using phase-shaped femtosecond ionizing laser pulses Hertz et al reported excitation of only odd J states of the O 2 molecule, and achieved alignment of 0.86 at 60K 24 . Experimental investigation of the nonadiabatic rotational excitation for ground state symmetric-top molecules, by two intense nonresonant ultrafast laser fields, leads to excitation of ∆J = 2 states if K = 0 while ∆J = 1 and ∆J = 2 if K > 0 25 . Hirokazu et al calculated the time evolution of the rotational-state distribution for NO molecules at varying pump intensities 26 .…”
Section: Introductionmentioning
confidence: 99%